Lookup-table-based DTC of induction machines with improved flux regulation and extended Kalman filter state estimator at low-speed operation - Alsofyani, I. M. (IEEE Computer Society, 2016)
Direct torque control (DTC) based on lookup table is known to have poor flux regulation at low speed that can cause a significant deterioration in the speed estimation of a sensorless drive. In this paper, stator flux regulation at low speed is improved under no load by replacing the hysteresis torque comparator with constant switching frequency controller, without any changes to the conventional lookup table; hence, the simple structure of DTC is maintained. In order to reduce the sampling time and hence improve the estimation process at very low speed, a simple fifth-order extended Kalman filter (EKF) is used in this paper. The fast execution time helps the linearization process of the EKF; hence, results in an improvement in its performance. Simulations and experimental results of the proposed sensorless drive system with the EKF estimator proves excellent flux regulation, and good speed robustness and stability at very low speed.